THE ACT OF ORAL COMMUNICATION IN ENGLISH AND UZBEK LANGUAGES - Yesmurzaeva Asel Abay qizi (Journals Park Publishing, 2023)
The thesis deals with the lexical, grammatical features of oral communication in English and Uzbek languages. Furthermore, the work is illustrated with sample.
Keywords: Oral communication, communicative action, spoken language, communication style, Communicative language Teaching (CLT), law.